تأثير تمرينات بمقاومات مختلفة في التحمل الخاص وبعض المتغيرات الكينماتيكية في انجاز عدو 400 حواجز متر - حبيب, رحيم رويح; عزيز, مي علي; محمد, رياض جاسم (Sulaimani Journal for Humanities, 2018)
This study aimed to prepare drills different weights in the development of the study variables in the preparation stage and identify the impact of these exercises in your endurance and some biomechanics’ variables and the completion of an race 400 meter hurdles, the researchers used the experimental method-style groups Equal, after he was homogeneity in the study variables (old training-your endurance biomechanics’ variables and the completion of an race 400 meters hurdles), as the results clearly showed that resistance exercises body weight and weight added to the body has undergone in the muscles involved in the rapid run efficiently and that helped achieve the rate of length and step frequency better, leading to develop the level of achievement.